The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1590/s1678-58782007000400003
|View full text |Cite
|
Sign up to set email alerts
|

A fast algorithm for inverse airfoil design using a transpiration model and an improved vortex panel method

Abstract: A fast algorithm for inverse airfoil design using an efficient panel method for potential flow calculation is presented. The method employs linear vortex distributions on the panels and a consistent procedure for imposing the Kutta condition, thus eliminating the spurious aerodynamic loading that usually appears at a cusped trailing edge. The algorithm searches the airfoil ordinates attending to a given surface velocity distribution with fixed abscissas. It begins with a guessed starting shape and successively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 12 publications
3
17
0
Order By: Relevance
“…The method as described before evaluates the relative velocity and its components on every panel of the airfoil surface and predicts the pressure coefficient, Cp, by calculating the influence coefficients and tangential velocity vector. The present panel method has been validated using the results obtained from the inverse design method, 6 Hess and Smith method 6 and analytical results of (Petrucci, 2007) as shown in Figure 7. The vortex panel method was implemented to verify the inverse design algorithm for the incompressible flows on a conformal mapped symmetric jukouwski airfoil having 10 % thickness.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The method as described before evaluates the relative velocity and its components on every panel of the airfoil surface and predicts the pressure coefficient, Cp, by calculating the influence coefficients and tangential velocity vector. The present panel method has been validated using the results obtained from the inverse design method, 6 Hess and Smith method 6 and analytical results of (Petrucci, 2007) as shown in Figure 7. The vortex panel method was implemented to verify the inverse design algorithm for the incompressible flows on a conformal mapped symmetric jukouwski airfoil having 10 % thickness.…”
Section: Resultsmentioning
confidence: 99%
“…The vortex panel method was implemented to verify the inverse design algorithm for the incompressible flows on a conformal mapped symmetric jukouwski airfoil having 10 % thickness. 6 It was revealed that source panel method implementation by Petrucci et al, showed geometric convergence problems for cambered airfoils. In his study, several iterations were required for geometric convergence in case of cambered airfoils in contrast to symmetric airfoils for different flow configurations.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It should be noted that the pure inverse design can be implemented by conformal mappings, streamline coordinatebased transformations, boundary integral formulations and Panel method [118]. Thus, it may be better to integrate the Panel method into the inverse airfoil design, especially for the CP prediction of the Darreius rotor [119].…”
Section: Proposed Inverse Design Approach Based On Panel and Cfd Methodsmentioning
confidence: 99%